Parental Discipline During Emerging Adulthood: A Person-Centered Approach. Issue 1 (January 2023) - McKinney, Cliff; Hovanec, Sarah E.; Szkody, Erica; Walker, Courtney S.
Although most parental discipline research examines the effects of discipline in children and adolescents, recent research has demonstrated that emerging adults continue to receive parental discipline. Importantly, a newly validated instrument for assessing discipline specifically during emerging adulthood has been created. Scales from this instrument include maternal and paternal approval, disappointment, and abuse, and these scales were associated with other parenting behaviors and psychological outcomes during emerging adulthood. However, a person-centered approach has not been conducted with this instrument. Given that discipline occurs at an idiographic level and that group norms inform such behaviors, a person-centered approach would identify highly informative emerging adult profiles based on patterns of discipline they receive from their parents. Thus, the current study utilized latent profile analysis (LPA) of 1110 participants attending a Southern United States university to identify emerging adult discipline profiles. These groups were then associated with parental and emerging adult psychological problems to gain an understanding of how these factors relate to different patterns of discipline across gender. Results best supported four profiles labeled as approving, distant, disappointed, and abusive. These groups reported increasingly higher parental and personal psychological problems across approving, distant, disappointed, and abusive profiles. Gender moderated some of these effects. Implications and future directions are discussed.